Dietary supplements for athletes: Emerging trends and recurring themes - Maughan, R. J.; Greenhaff, P. L.; Hespel, P. (Journal of Sports Sciences, 2011)
Dietary supplements are widely used at all levels of sport. Changes in patterns of supplement use are taking place against a background of changes in the regulatory framework that governs the manufacture and distribution of supplements in the major markets. Market regulation is complicated by the increasing popularity of Internet sales. The need for quality control of products to ensure they contain the listed ingredients in the stated amount and to ensure the absence of potentially harmful substances is recognized. This latter category includes compounds prohibited under anti-doping regulations. Several certification programmes now provide testing facilities for manufacturers of both raw ingredients and end products to ensure the absence of prohibited substances. Athletes should carry out a cost-benefit analysis for any supplement they propose to use. For most supplements, the evidence is weak, or even completely absent. A few supplements, including caffeine, creatine, and bicarbonate, are supported by a strong research base. Difficulties arise when new evidence appears to support novel supplements: in recent years, ß-alanine has become popular, and the use of nitrate and arginine is growing. Athletes seldom wait until there is convincing evidence of efficacy or of safety, but caution is necessary to minimize risk.